Current regulatory (draft) guidance on chiral medicinal products: Canada, EEC, Japan, United States - Rauws, A G; Groen, K (Chirality (New York, N.Y.), 1994)
The rapid development of stereospecific analytical, synthetic, and preparative methods has profoundly changed the prospects for development and application of chiral medicinal products. This has induced regulatory agencies, e.g., in Canada, the EEC, Japan, and the United States, to prepare guidance on this subject. The present draft documents are discussed, with emphasis on the two most important cases: (1) New racemates: How many extra requirements are justified? (2) Development of a single enantiomer from an approved racemate: how few are acceptable? At the moment the opportunities for early harmonisation are favourable and the formulation of one international guidance document seems feasible.